ANALISIS POSISI PRODUK KARTU GSMDENGAN METODE MULTIDIMENSIONAL SCALLING (MDS)PADA MAHASISWA FMIPA UNIVERSITAS NEGERI SURABAYA - RADITYA PANCA W (Universitas Negeri Surabaya, 2013)
GSM cellular business growth (Global System for Mobile Communication) is growing rapidly. The increasing demand for mobile phone simcard lead demand is high enough to get a lot of consumers are more companies offering features, bonuses and so on, so that they can dominate the sales market. One theory is used to solve the Masalha is the method of multidimensional scaling. This study aims to analyze the position of products which include the mobile operator, SIMPATI, IM3, MENTARI, AXIS, XL, and THREE using Multidimensional Scaling analysis, the Student Faculty UNESA. Data were obtained from questionnaires .. The result of the calculation is known that the questionnaire had been valid and reliable (reliably) with a correlation coefficient above 0.5 and Cronbach alpha values greater than 0.8. Furthermore, the data were analyzed by using multidimensional scaling analysis and test STRESS. Obtained from the analysis of the spatial map showing the seventh position with a GSM operator STRESS value of 6.4%. Results of multidimensional scaling analysis shows that the U.S. has its closest competitor SIMPATI, IM3 has MENTARI closest competitor. THREE has the closest competitor, namely AXIS and XL.Keywords: GSM operators, Multidimensional Scaling